2011
DOI: 10.2967/jnmt.111.090027
|View full text |Cite
|
Sign up to set email alerts
|

Is Liver SUV Stable over Time in 18F-FDG PET Imaging?

Abstract: This work investigated whether 18 F-FDG PET standardized uptake value (SUV) is stable over time in the normal human liver. Methods: The SUV-versus-time curve, SUV(t), of 18 F-FDG in the normal human liver was derived from a kinetic model analysis. This derivation involved mean values of 18 F-FDG liver metabolism that were obtained from a patient series (n 5 11), and a noninvasive population-based input function was used in each individual. Results: Mean values (695% reliability limits) of the 18 F-FDG uptake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…Furthermore, the conspicuity and detectability of the tumor partly also depend on the postinjection time. A later scan could potentially provide a higher contrast-tonoise ratio in malignant lesions (22). In our study, 10 of 12 lesions missed at 40% PET non-TOF were imaged before PET/ CT.…”
Section: Nuclear Medicine: Fdg Dose Reduction In Pet/mr Imaging Sekinmentioning
confidence: 81%
“…Furthermore, the conspicuity and detectability of the tumor partly also depend on the postinjection time. A later scan could potentially provide a higher contrast-tonoise ratio in malignant lesions (22). In our study, 10 of 12 lesions missed at 40% PET non-TOF were imaged before PET/ CT.…”
Section: Nuclear Medicine: Fdg Dose Reduction In Pet/mr Imaging Sekinmentioning
confidence: 81%
“…For the healthy liver, which reversibly traps 18 F-FDG, the [AUC NIF / λ C pN ( t )] ratio is 164 min, for peak activity at about t = 55 min (Figure two in [19]). Total peak activity is 8.6 kBq/mL, and hence SUV uncorr ( t peak ) = 1.7 g.mL -1 , a value identical to that obtained by Minamimoto et al [17].…”
Section: Resultsmentioning
confidence: 99%
“…Healthy lung irreversibly traps 18 F-FDG and F is not negligible in comparison with the ratio K / (λ + k R ): 63% at peak time [18]. Healthy liver reversibly traps 18 F-FDG and F is not negligible in comparison with the ratio K / (λ + k R ): 26% at peak time [19]. Furthermore, it should be noted that neglecting reversibility of the 18 F-FDG uptake in healthy brain and liver leads to an overestimation of integrated activity that can be approached by comparing the [AUC NIF / λ C pN ( t peak )] ratio obtained at t = 62 and 55 min to that obtained at t = 79 min (=269/187 and 269/164), which differs by 44% and 64%, respectively: the greater the release rate constant, the greater the overestimation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prospective study by Laffon et al performed PET acquisition at two time points on the same day and reported that the decay-corrected SUV of the liver remains nearly constant if the time delay between tracer injection and PET acquisition is in the range of 50–110 min. [17] This suggests that in clinical practice, liver SUV can be used for comparison with SUV of suspected malignant lesions, if comparison is made within this timeframe.…”
Section: Discussionmentioning
confidence: 99%